Survival and associated factors among patients with oral squamous cell carcinoma (OSCC) in Mulago hospital, Kampala, Uganda - Asio, Juliet; Kamulegeya, Adriane; Banura, Cecily (CrossMark, 2018)
Abstract Background: Despite improvements in diagnosis and patient management, survival and prognostic factors of patients with oral squamous cell carcinoma (OSCC) remains largely unknown in most of Sub Saharan Africa. Objective: To establish survival and associated factors among patients with oral squamous cell carcinoma treated at Mulago Hospital Complex, Kampala. Methods: We conducted a retrospective cohort study among histologically confirmed oral squamous cell carcinoma (OSCC) patients seen at our centre from January 1st 2002 to December 31st 2011. Survival was analysed using Kaplan-Meier method and comparison between associated variables made using Log rank-test. Cox proportional hazards model was used to determine independent predictors of survival. P-values of less than 0.05 were considered statistically significant. Results: A total of 384 patients (229 males and 155 females) were included in this analysis. The overall mean age was 55.2 (SD 4.1) years. The 384 patients studied contributed a total of 399.17 person-years of follow-up. 111 deaths were observed, giving an overall death rate of 27.81 per 100 person-years [95% CI; 22.97–32.65]. The two-year and five-year survival rates were 43.6% (135/384) and 20.7% (50/384), respectively. Tumours arising from the lip had the best five-year survival rate (100%), while tumours arising from the floor of the mouth, alveolus and the gingiva had the worst prognosis with five-year survival rates of 0%, 0% and 15.9%, respectively. Independent predictors of survival were clinical stage (p = 0.001), poorly differentiated histo-pathological grade (p < 0.001), male gender (p = 0.001), age > 55 years at time of diagnosis (p = 0.02) and moderately differentiated histo-pathological grade (p = 0.027). However, tobacco & alcohol consumption, tumour location and treatment group were not associated with survival (p > 0.05). Conclusions: The five-year survival rate of OSCC was poor at 20.7%. Male gender, late clinical stage at presentation, poor histo-pathological types and advanced age were independent prognostic factors of survival. Early detection through screening and prompt treatment could improve survival. Keywords: Oral squamous cell carcinoma, Uganda, Survival, Clinical-pathological presentation
Keywords: oral squamous cell carcinoma (OSCC); Survival